MRI diagnosis of carpal boss and comparison with radiography. (October 2017) - Mespreuve, Marc; De Smet, Luc; De Cuyper, Kristof; Waked, Karl; Vanhoenacker, Filip
Background: A carpal boss is a potentially painful bony mass in the region of the second or third carpometacarpal joint. The combination of clinical examination and radiography is usually sufficient for the diagnosis. Purpose: To determine whether magnetic resonance imaging (MRI) examination of the quadrangular joint can assist the diagnosis of persistent pain near a carpal boss. Material and Methods: Fifty-seven patients with a carpal boss were retrospectively reviewed using MRI and conventional radiographs and compared to an asymptomatic control group. Results: MRI demonstrated a variable morphology and a variety of bone and soft tissue abnormalities associated with carpal boss. Bone marrow edema around the quadrangular joint shows a significant correlation (Fisher's exact test: P  < 0.001) and a positive correlation (Pearson's test r = 0.632, significant at the 0.01 level [two-tailed]) with a painful carpal boss. Conclusion: MRI offers detailed examination of bone and soft tissue abnormalities associated with a carpal boss. Local bone marrow edema strongly correlates with a painful carpal boss.